2015
DOI: 10.1080/09515070.2015.1090395
|View full text |Cite
|
Sign up to set email alerts
|

The role of maladaptive anger in self-criticism: A quasi-experimental study on emotional processes

Abstract: The present study examines the role of emotion in the self-critical process of individuals with anger problems. Self-criticism is a prevalent intra-personal feature which greatly impacts an individual's emotion. So far, it is unclear, which emotions individuals with maladaptive anger experience when they work through their self-criticism. Using a quasi-experimental design, the present study compared n = 23 anger-prone under-graduate students to n = 22 controls on process indices of contempt, fear, shame, anger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 47 publications
5
41
0
Order By: Relevance
“…Pre-post treatment decrease in arousal was associated with symptom reduction, whereas the arousal peaked at both assessment points right after the imagery task in the behavioral assessment of emotional processing (sub-step 1 of the self-criticism task). This result is consistent with an earlier study using a similar assessment procedure (i.e., a two-chair dialogue for emotion-focused therapy; Kramer and Pascual-Leone (2016). This pattern -withinassessment increase in arousal and between-assessments decrease in arousal -has already been observed in research on emotional processing, using a repeated expressive writing paradigm for traumatic memories .…”
Section: Neurobehavioral Change In Bpd 18supporting
confidence: 91%
See 1 more Smart Citation
“…Pre-post treatment decrease in arousal was associated with symptom reduction, whereas the arousal peaked at both assessment points right after the imagery task in the behavioral assessment of emotional processing (sub-step 1 of the self-criticism task). This result is consistent with an earlier study using a similar assessment procedure (i.e., a two-chair dialogue for emotion-focused therapy; Kramer and Pascual-Leone (2016). This pattern -withinassessment increase in arousal and between-assessments decrease in arousal -has already been observed in research on emotional processing, using a repeated expressive writing paradigm for traumatic memories .…”
Section: Neurobehavioral Change In Bpd 18supporting
confidence: 91%
“…The second sub-step involves the patient adopting the stance of the inner self-critical voice and express self-criticism (from a different chair, the "self-critical" one), addressed to the self, as imagined on the initial chair (Whelton & Greenberg, 2005;Greenberg, 2002). The third sub-step involved for the patient (and back again on the initial chair) describes her current emotional reaction to the self-criticism (for a complete description of the two-chair dialogue used in research, see Kramer and Pascual-Leone (2016). This assessment lasted 30 minutes and was conducted pre-and post-therapy.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that this process relates to healthy functioning and a good outcome from psychotherapy [34], in particular the flexibility of emotional experiences [47]. The relevance of this dynamic conception of emotion processing to BPD was supported in terms of change in anger processing [48] and in terms of change in undifferentiated global distress [27]. It was shown to also be of relevance in narcissistic and histrionic PDs [49,50].…”
Section: Mechanisms Of Change In Treatments For Borderline Personalitmentioning
confidence: 91%
“…This transformation conception may explain the resolution of harsh self-criticism, a central clinical feature of BPD [48,[51][52][53]. Whelton and Greenberg (2005) proposed a paradigm of studying emotion transformation related to self-criticism using the empty-chair dialogue.…”
Section: Mechanisms Of Change In Treatments For Borderline Personalitmentioning
confidence: 99%
“…In order to respond to the first implication above of a transdiagnostic approach to measurement of self‐contempt, Kramer and Pascual‐Leone () sought to assess self‐contempt as it appears during the clinical process, basing their criteria on prior work by Whelton and Greenberg (), Ekman and Friesen () and Gottman (). They used a 3‐point anchored Likert‐type scale, to be applied in session video as a continuous moment‐by‐moment assessment.…”
Section: Assessing Self‐contempt: Using Observation In Contextmentioning
confidence: 99%